(untitled) (Bangladesh Journal of Medical Science, 2023)
Background: In order to tackle COVID-19 pandemic and the emerging variants, researchers around the globe have investigated many vaccine candidates from different manufacturers, however vaccine development is not an easy task but is a top priority to restore normalcy as represented a step to achieve the desired herd immunity threshold. Patients and methods: in this study we assessed and compared the level of IgG anti-RBD neutralizing antibodies triggered from each vaccine against SARS-CoV2 infection in 123 vaccinated subjects, by using isotypeand species- free competitive blocking ELISA. Blood samples were taken from vaccinated individuals 1 and 8 months after the second dose of the vaccines. Results: the findings of the current study revealed that two-dose vaccination might be effective to trigger robust humoral neutralizing immunity at 1month and even durable for as long as 8months with different sustained levels among the three studied previously mentioned vaccines. The serum level of the neutralizing IgG antibodies, Pfizer group revealed the highest level compared to AstraZeneca and Sinopharm groups (P<0.05); the Sinopharm showed trend of higher levels of neutralizing antibodies than AstraZeneca but without reaching statistical significance (P>0.05). Additionally, the serum level of neutralizing IgG antibodies, which represent the humeral immunity to SARSCoV- 2, was shown to be far higher in 1-month than in 8-month post-2nd dose vaccination groups (P<0.0001). Conclusion: Altogether, it is concluded that Pfizer vaccine proved to be of highest and most durable neutralizing anti-RBD IgG antibodies and followed with Sinopharm and AstraZeneca vaccines. Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 553-563